Strategy or disaster: New-style river regulation as an issue of national security - Schweitzer, Ferenc (Hungarian Geographical Bulletin, 2015)
Protection against floods along the Tisza, Danube and their major tributaries have become an issue of state security significance since nearly 2.5 million lives are affected. The floods of 1999 and 2000 on the Tisza and the 2013 flood on the Danube demonstrated that the 150-year-old system was corrected at the expense of outstanding financial investment and human effort although it is clear that the flood-protection structures built observing contemporary prescriptions are not able to provide the necessary protection. With the rising flood levels and other reasons (including climate change, tectonic movements, changes in river mechanism and others), their protection potential will be further reduced in the future. The warning signs are getting more and more frequent. Since 1864 there have been almost 30 disastrous floods on the Tisza alone. Over the past quarter of a century there happened ten high floods, during which the flood-control system could not ensure the safe conveyance of flood waves. The changes on the Danube were also very remarkable in spite of the major water engineering interventions along the Hungarian section of the river.